On Construction and Verification of PLC-Programs - E. V. Kuzmin; V. A. Sokolov (Моделирование и анализ информационных систем, 2012)
We review some methods and approaches to programming discrete problems for Programmable Logic Controllers on the example of constructing PLC-programs for controling a code lock. For these approaches we evaluate the usability of the model checking method for the analysis of program correctness with respect to the automatic verification tool Cadence SMV. Some possible PLC-program vulnerabilities arising at a number approaches to programming of PLC are revealed.